ICT solutions in intelligent organizations as challenges in a knowledge economy = Rozwiązania ICT w organizacjach inteligentnych jako wyzwanie gospodarki opartej na wiedzy - Adamczewski, Piotr (Zielona Góra: Faculty of Economics and Management Press)
Solutions of the Information and Communication Technology (ICT) are the foundation of modern economic organizations in a knowledge economy. This is the case in particular in intelligent organizations, for which the advanced ICT infrastructure is the sine qua non condition for the effective knowledge management. This article is aimed at describing the role of modern ICT trends, which are described as SMAC, (Social, Mobility, Analytics, Cloud), and are becoming an essential ICT element supporting management processes.
Keywords: ITC; organizacja inteligentna; gospodarka oparta na wiedzy; SMAC; małe i średnie przedsiębiorstwa; intelligent organization; knowledge economy; small and medium enterprises (SME)